2023
DOI: 10.3390/ijms24076764
|View full text |Cite
|
Sign up to set email alerts
|

Erucin, an H2S-Releasing Isothiocyanate, Exerts Anticancer Effects in Human Triple-Negative Breast Cancer Cells Triggering Autophagy-Dependent Apoptotic Cell Death

Abstract: Breast cancer is the most frequent form of cancer occurring in women of any age. Among the different types, the triple-negative breast cancer (TNBC) subtype is recognized as the most severe form, being associated with the highest mortality rate. Currently, there are no effective treatments for TNBC. For this reason, the research of novel therapeutics is urgently needed. Natural products and their analogs have historically made a major contribution to pharmacotherapy and the treatment of various human diseases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Furthermore, ERU exhibited a cardioprotective effect in an in vivo model of I/R injury through direct persulfidation of mitoKv7.4 channels, unequivocally confirming the link between the cardioprotective effects of ERU and the H 2 S released from the isothiocyanate moiety [33]. Moreover, ERU was found to inhibit the tumor growth in human triple-negative breast cancer cells [52] as well as in a breast cancer cell xenograft mouse model; interestingly, in this case a regulation of mitochondrial fission/fusion emerges, in particular with the translocation of cofilin and Drp1 and consequent cell apoptosis [53].…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, ERU exhibited a cardioprotective effect in an in vivo model of I/R injury through direct persulfidation of mitoKv7.4 channels, unequivocally confirming the link between the cardioprotective effects of ERU and the H 2 S released from the isothiocyanate moiety [33]. Moreover, ERU was found to inhibit the tumor growth in human triple-negative breast cancer cells [52] as well as in a breast cancer cell xenograft mouse model; interestingly, in this case a regulation of mitochondrial fission/fusion emerges, in particular with the translocation of cofilin and Drp1 and consequent cell apoptosis [53].…”
Section: Discussionsupporting
confidence: 52%
“…The effect has been reported to be concentration-dependent [7]. The effect of H 2 S and H 2 S donors in cancer has been widely reported in several experimental studies and, similarly to what observed for Met, it seems to act via several mechanisms ranging from the alteration of the cell cycle and the DNA replication pathway [47] to apoptotic cell death [48] induced via the inhibition of ERK1/2 phosphorylation [20], the attenuation of ferroptosis [49] or autophagy [19]. Among the different H 2 S donors, isothiocyanates are well known for their peculiar epigenetic anti-cancer effect, linked to their ability to inhibit histone deacetylases (HDACs) enzymes [50,51].…”
Section: Discussionmentioning
confidence: 71%
“…Also, erucin demonstrated to have anti-proliferative activity in human lung adenocarcinoma A549 cells through the induction of p53, p21 and PARP-1 cleavage [71]. Recently, erucin was demonstrated to have anticancer effects in an in vitro model of triple-negative breast cancer (TNBC) subtype by inducing apoptosis and autophagy, having also antimetastatic activity [72]. In an in vitro model of renal cancer, erucin induced a concentration-dependent decrease in cell viability and cell-cycle arrest at G2/Mitosis [24].…”
Section: Glucoerucin (Ge) and Erucinmentioning
confidence: 99%